2018
DOI: 10.3390/su10030871
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Droughts during Crop Growing Seasons of Nigeria

Abstract: This study assesses the impacts of recent climate changes on drought-affected areas and the occurrence of droughts during different cropping seasons of Nigeria using the standardized precipitation evapotranspiration index (SPEI). The crop growing seasons are considered because the droughts for those periods are more destructive to national agricultural production. The Mann–Kendall test and binary logistic regression were used to quantify the trends in drought-affected areas and the occurrence of crop droughts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 123 publications
(59 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…The gauge-based gridded climate data are widely used as a proxy of observed precipitation and PET data around the world (Shiru et al, 2018). Over the last 2 decades, several gauge-based gridded datasets have been developed and applied for different purposes (Li et al, 2014).…”
Section: Datasetsmentioning
confidence: 99%
“…The gauge-based gridded climate data are widely used as a proxy of observed precipitation and PET data around the world (Shiru et al, 2018). Over the last 2 decades, several gauge-based gridded datasets have been developed and applied for different purposes (Li et al, 2014).…”
Section: Datasetsmentioning
confidence: 99%
“…For example, Shiru et al . () reported an increase in the frequency of small areal extent droughts, but a decrease in large areal extent droughts in Nigeria. Therefore, it is important to assess the changes in spatial extents of different drought features.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, climate change can alter the spatial distribution of rainfall and thus the spatial extent of droughts (Sobral et al, 2018). For example, Shiru et al (2018) reported an increase in the frequency of small areal extent droughts, but a decrease in large areal extent droughts in Nigeria. Therefore, it is important to assess the changes in spatial extents of different drought features.…”
Section: Introductionmentioning
confidence: 99%
“…Though reliability in trends obtained using gridded data has been reported in many studies [3,[5][6][7][8], uncertainty in results is still a major issue. Gridded climate data can be broadly classified as gauge-based, remote-sensing based, reanalysis, or a hybrid of those methods [9].…”
Section: Introductionmentioning
confidence: 99%
“…The present study adopted the Sen's slope as an estimator of the magnitude of change and the Mann-Kendall (MK) and modified Mann-Kendall (mMK) tests to assess the significance of change at a 95% level of confidence. The mMK method has been found robust in the estimation of trends in the presence of short-and long-term autocorrelations in rainfall data [3,6,8,14]. Therefore, it can provide a unidirectional trend in time series by removing the natural variability of climate.…”
Section: Introductionmentioning
confidence: 99%